Perirenal Fat and Chronic Kidney Disease: A Systematic Review and Meta-Analysis - Pengfei Kang; Boju Sun; Jing Hao; Conghui Wang; Xiangmei Chen (Kidney & Blood Pressure Research)
Introduction: Although previous studies have investigated the impact of perirenal fat on chronic kidney disease (CKD), there are yet no systematic reviews and meta-analyses to investigate the association between perirenal fat and CKD. Methods: We searched six English electronic databases including PubMed, Scopus, Web of Science, Ovid, Embase, and the Cochrane Library to select clinical studies that reported the relationship between perirenal fat and CKD, and the search period ranged from the establishment of the database to September 10, 2024. Two researchers independently screened the studies and ultimately compared the literature. Stata (version 16 SE; College Station, TX, USA) software was used for statistical analysis. Results: A total of eight articles that included 2,576 patients were included in this meta-analysis. The results showed a significant association between perirenal fat and CKD (95% CI: 0.48–0.65, p = 0.00), and no heterogeneity was detected between these two groups (I2 = 31.06%, p = 0.18). Subgroup analysis revealed that whether it is diabetic nephropathy, nephropathy caused by abnormal cardiac function, or primary CKD, perirenal fat is closely related to them. Conclusion: The results of this systematic review and meta-analysis showed that perirenal fat thickness is closely related to CKD. Clinicians should pay attention to relevant indicators when diagnosing and treating patients with CKD.